A new cumacean (Crustacea) genus from beaches of Golfo de Nicoya, Costa Rica - Walting, Les; Breedy, Odalisca (Revista de Biología Tropical, 1988)
Coricuma nicoyensis gen.et sp. nov. (Crustacea, Cumacea) is described from material collected during 1984 at the Punta Morales intertidal mud flat (> 30% silt + clay), Gulf of Nicoya (10° N, 85° W), Costa Rica. The exact placement of the new genus is problematical and for the present time is assigned to the Bodotriinae. This is the sixth cumacean described from the Pacific coast of the Americas between California and Tierra del Fuego.